Systemic organization of Tetraponera rufonigra (Jerdon, 1851) (Hymenoptera: Formicidae): histological observation - Naphat Somala,; Sinlapachai Senarat,; Chamnan Para,; Wannee Jiraungkoorskul,; Gen Kaneko,; Thitiya Poonpet,; Pisit Poolprasert, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2020)
Tetraponera rufonigra Jerdon, 1851, is one of the most dangerous ants, whose apex of gaster region contains a sting structure with a complex venom gland. Here, we describe the systemic organ system of T. rufonigra using histological techniques. The venom gland of T. rufonigra was located above the mesentero-proctodeal region, which could be histologically classified into two parts; the venom gland reservoir and the venom gland tubes. The venom gland tubes were lined by a simple cuboidal epithelium, whereas the venom gland reservoir was enclosed with simple squamous epithelium. The pygidial gland was localized near the cuticle as clusters, and each of the oval shape pygidial gland cells contained a spherical nucleus surrounded by acidophilic cytoplasm. High magnification observation showed that the integumentary system consists of three layers; epicuticle, exocuticle, and endocuticle. The digestive system was a single narrow tube consisting of the foregut, midgut, and hindgut. Five to six rectal papillae were found in the hindgut. The urinary system was made up of Malpighian tubules, which lined with simple cuboidal epithelium and tracheal embedded in the adipose tissue. The respiratory system was composed of spiracles and trachea adjacent to the integument, all of which were surrounded by a simple squamous epithelium. In the nervous system, several ganglia were found in this study. There were two layers in each ganglion: outer cortex and inner medullar layers. Several cell types were observed in the cortex layer including the neurosecretory cells, the neuroglia, and neurons. The outcomes of this study could provide a useful basis for future research on the family Formicidae.